Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/ipd.12249
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among α amylase and carbonic anhydrase VI in saliva, visible biofilm, and early childhood caries: a longitudinal study

Abstract: The presence of visible biofilm and low salivary activity of α amylase may be considered risk predictors for ECC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 38 publications
4
53
0
5
Order By: Relevance
“…In this context, Borghi et al revealed a direct relationship between α-amylase and CA VI from saliva, the visible bacterial biofilm, and early childhood caries. This longitudinal study found that CA VI activity was significantly higher in saliva of children with caries (P ≤ 0.05), and that α-amylase activity was significantly higher in saliva of caries-free children (P < 0.0001) ( Table 7) [71]. In the same framework, Colgate-Palmolive Company patented a kit diagnosing the amplified predisposition to enamel erosion in a mammal based on two methods, both measuring and quantifying the concentrations of proteins critical to proper enamel formation.…”
Section: Carbonic Anhydrase VI As a Disease Biomarkermentioning
confidence: 82%
“…In this context, Borghi et al revealed a direct relationship between α-amylase and CA VI from saliva, the visible bacterial biofilm, and early childhood caries. This longitudinal study found that CA VI activity was significantly higher in saliva of children with caries (P ≤ 0.05), and that α-amylase activity was significantly higher in saliva of caries-free children (P < 0.0001) ( Table 7) [71]. In the same framework, Colgate-Palmolive Company patented a kit diagnosing the amplified predisposition to enamel erosion in a mammal based on two methods, both measuring and quantifying the concentrations of proteins critical to proper enamel formation.…”
Section: Carbonic Anhydrase VI As a Disease Biomarkermentioning
confidence: 82%
“…Existen evidencias sobre la relación inversa entre los niveles de mucina en la saliva y la incidencia de caries 12,44 . En un estudio se compararon la actividad de αamilasa y otros parámetros salivales en niños libres de caries con niños con caries activas y se observó que el pH, la capacidad buffer y el nivel de calcio y fósforo aumentaron con la disminución de la actividad de caries en los niños, mientras que la actividad de α-amilasa se incrementó con el aumento de la actividad de caries 45,46 . Esto estaría relacionado con su actividad enzimática específica en la PA y en el biofilm cariogénico 19,47 .…”
Section: A) Cariesunclassified
“…High sugar consumption is the primary risk factor [1]. There are multiple predisposing factors for ECC including those that increase the risk for high consumption of sugar, and those that increase tooth susceptibility to caries [2][3][4][5]. These factors have largely been studied at the individual level.…”
Section: Introductionmentioning
confidence: 99%